Hubungan Antara Penyesuaian Diri Dengan Stres Akademik Pada Mahasiswa Perantau di Universitas Negeri Makassar - Afrialdy, Muh; A, Ahmad; Akmal, Nur (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Students who study away from their hometown generally are individuals who live in another area to seek knowledge at higher education institutions in a new area and prepare themselves for academic achievement. This can trigger academic stress. This study aims to uncover the relationship between self-adjustment and academic stress among migrant students at the Faculty of Psychology, Makassar State University. A total of 321 individuals were determined using accidental sampling technique as respondents. Self-adjustment and academic stress scales are the measuring tools used in this study. The data analysis used in this study is the Pearson product moment correlation processed using SPSS 24.0 for windows. The results of this study show that there is a significant negative relationship between self-adjustment and academic stress among migrant students at the Faculty of Psychology, Makassar State University (r = -0.165, p = 0.003 < 0.05), indicating that the higher the self-adjustment score, the lower the academic stress among migrant students at the Faculty of Psychology, Makassar State University. This study can be a foundation for migrant students that provides the potential for individuals to apply self-adjustment at campus as a practice in stabilizing academic stress